Endoscopic Excision of Third Ventricle Choroid Plexus Papilloma - Lavlesh Rathore; Debabrata Sahana; Sanjeev Kumar; Rajiv K. Sahu (Indian Journal of Neurosurgery)
Choroid plexus papilloma is a rare intraventricular tumor in children. Its management poses a challenge. Here we describe such a case of third ventricular choroid plexus papilloma and its endoscopic excision through a single burr hole. A 1-year-old child presented with headache, vomiting, and a large head with sunset sign and tense fontanel. Computed tomography (CT) and magnetic resonance imaging brain plain and contrast revealed dilated ventricles with a frondlike mass in the third ventricle with intense contrast enhancement, suggestive of choroid plexus papilloma of the third ventricle. The lesion was excised completely using an endoscope placed through a single burr hole at the right Kocher's point. Postoperative recovery was uneventful. The child was relieved of his symptoms. CT scan revealed complete removal of the lesion. Histopathology confirmed the diagnosis of choroid plexus papilloma. We document our surgical experience and present an edited video of the surgery. The key steps and nuances are described in the audio timeline. The authors acknowledge the feasibility of performing this complex surgery via a minimally invasive method, which has not been accepted routinely for this pathology.